ChemInform Abstract: Synthesis and Characterization of Ba[CoSO]: Magnetic Complexity in the Presence of Chalcogen Ordering. Issue 41 (October 2015) - Valldor, Martin; Roessler, Ulrich K.; Prots, Yurii; Kuo, Chang‐Yang; Chiang, Jen‐Che; Hu, Zhiwei; Pi, Tun‐Wen; Kniep, Ruediger; Tjeng, Liu Hao
Abstract Ba[CoSO] is prepared by the reaction of equimolar amounts of BaO, Co, and S (corundum crucible in evacuated silica tubes, 1.